Respon Islam Terhadap Modernitas Barat - Nurrohmah, Nurrohmah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Modernity is a novelty that is applied in life. This includes; way of thinking, behaving and in everyday human life. This modernity is part of a historical sequence in the course of history. This modernity is closely related to the symptoms of secularism in society. The consequence is that religious dogmas that were originally sacred are then deconstructed by their adherents by adjusting to the times, so that religion becomes profane. Today modernity is applied by all circles, even among Muslims. Therefore, this article discusses how Islam responds to modernity from the West. Because, in Islam there are camps that accept and reject. Those who accept are based on the opinion that modernity can be adapted to the Qur'an according to the times, while those who reject it argue that modernity is a Western product and eliminates religious values. Keywords: Response, Islam, and Modernity